Pengetahuan dan sikap rakan sebaya terhadap pelajar kurang upaya di sebuah IPTA di Malaysia - Hasnah Toran,; Tajul Arifin Muhamad,; Mohd Hanafi Mohd Yasin,; Mohd Mokhtar Tahar,; Nur Hazwani Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Negative attitudes towards people with disabilities (PWD) form barriers for them to participate fully in society. This study investigated the level of knowledge of students in a local institute of higher education about PWD and to study students’ perceptions and attitudes towards their peers with disabilities. There were 120 respondents from 12 faculties for this research who were selected through a tiered random sampling method. Data was collected through questionnaires and later analyzed statistically. Findings from this research showed that the level of knowledge of PWD among respondents was moderate. Perceptions and attitudes of respondents towards PWD were moderately positive. This research suggested that a high level of knowledge and exposure of PWD may have a positive impact on students’ perceptions and attitudes towards peers with disabilities.Research implications and suggestions for future studies were presented for further action by those who may be interested to venture further into this area. It is hoped that this research will provide input that will be beneficial to heighten the awareness of PWD that will lead to their full acceptance by society on campus